Fuzzy Control of Hydrogen Generation by the Reaction of Activated Aluminum Particles and Water - Giap, Bui Trong; Takahara, Kenji; Kajiwara, Toshinori; Maekawa, Koji (International Journal of Natural Sciences Research, 2017)
The purpose of this paper is to design a fuzzy control system for generating hydrogen at a desired level by a reaction between water and activated aluminum particles. The activated aluminum particles are produced shredded aluminum sawdust. It is difficult to characterize the reaction quantitatively because the characteristics of hydrogen generating reaction vary as depending on the samples, the environment of the reaction and so on. The experimental system consists of a fuel cell (FC) of 100[W], a water tank, a reaction vessel, pressure sensors, a water pump, a radiator and a one-chip microcomputer. The fuzzy control system is designed to determine the quantum of water which is supplied to the activated aluminum particles. The error forms a desired value of the pressure of the reaction vessel and the change of the error are chosen as the labels of the fuzzy membership functions. The proposed fuzzy control system is applied to maintain the pressure of the reaction vessel of the developed hydrogen generation system at a certain level. The developed hydrogen generation system is confirmed to provide hydrogen to the FC by experiments under various conditions.